Post Mortem Study of Alcoholic and Non-Alcoholic Liver Diseases in Ajmer Region - Porwal, Vandana; Mishra, Neha; Jain, Deepali; Gupta, Seema (Annals of Pathology and Laboratory Medicine, 2020)
Background: Most of the chronic liver diseases even in advanced stage may cause no prominent clinical signs or symptoms. They either go undiagnosed or are found incidentally during general health check-ups, investigations for other diseases, surgery, or autopsy. The underlying causes of chronic liver diseases vary in different geographic areas and are based on various factors such as socioeconomic status, life style, diet, local or regional infections, and other endemic diseases. The aim of our study is to establish prevalence of silent liver diseases like NASH and alcoholic liver disease and its correlation with age, sex, lifestyle and other factors in local population. Methods: 146 Post-mortem specimens of liver were received in Department of Pathology, J.L.N. Medical College, Ajmer from January 2018 to August 2018. 27 cases were excluded due to autolysis. Information regarding age, sex, marital status, place, food habit, alcoholic usage and previous history of any disease were collected in whenever cases possible. Processed tissue sections were stained and were analysed by descriptive statistics. Result: Total 119 cases of liver were included. The age ranged from 11-90 years with mean age 42.14 Â±13.12 years. Majority of patients belonged to the 4th decade of life, followed by 5th decade with male preponderance (M:F ratio 5:1). Maximum number of cases was of steatosis with grade I and IV. Important findings included steatosis in 58 (48.74%), steatohepatitis in 12 (10.08%), chronic hepatitis in 36 (30.25%), confluent necrosis in 8 (6.72%), cirrhosis in 5 (4.2%) cases. Conclusion: Silent diseases of the liver like NASH are not uncommon. Steatosis and chronic hepatitis comprise a significant finding in our locality.